Electric field fluctuations in the two-dimensional Coulomb fluid - Callum Gray; Steven T Bramwell; Peter C W Holdsworth (New Journal of Physics, 2021)
The structure factor for electric field correlations in the two dimensional Coulomb fluid is simulated and compared to theories of the dielectric function. Singular changes in the structure factor occur at the Berezinskii–Kosterlitz–Thouless insulator to conductor transition, as well as at a higher temperature correlation transition between a poor electrolyte and perturbed Debye–Hückel fluid. Structure factors are found to differ in the canonical and grand canonical ensembles, with the poor electrolyte showing full ensemble inequivalence. We identify mechanisms of ‘underscreening’ and ‘pinch point’ scattering that are relevant to experiments on ionic liquids and artificial spin ice respectively.